Crossed-Dipole-Shaped Metasurface Transmissive Linear-to-Circular Polarization Converter - Nkimbeng, Cho Hilary Scott; Wang, Heesu; Park, Ikmo (15th Global Symposium on Millimeter-Waves and Terahertz, GSMM 2024 - Proceedings, 2024)
This paper presents a single-layer wideband linear-to-circular (LTC) polarization converter implemented with a crossed-dipole-shaped metasurface. The LTC polarization converter is placed on the top side of a single-substrate layer. The proposed design yields a nearly equal transmission amplitude and steady phase difference of nearly 90° between the two orthogonal components of electromagnetic waves transmitted across a wide frequency range. The numerical results demonstrate that the polarizer can accomplish wideband LTC polarization conversion at both x- and y-polarized incident waves within a frequency range of 12.1-30.2 GHz, which represents a fractional bandwidth of 85.6%. Furthermore, the proposed LTC polarization converter achieves a high total transmittance of electromagnetic waves.
Keywords: Axial ratio; Crossed dipoles; Metasurface; Polarization conversion; Polarization conversion surface; Polarization converters; Single layer; Substrate layers; Transmission coefficients; Wide-band; Axial ratio; circular polarization; crossed dipole; metasurface; polarization conversion surface; transmission coefficient